Frontispiece: Terpyridine‐Based 3D Metal–Organic‐Frameworks: A Structure–Property Correlation. Issue 19 (2nd April 2021) - Elahi, Syed Meheboob; Raizada, Mukul; Sahu, Pradip Kumar; Konar, Sanjit
Abstract : 4'‐Phenyl terpyridine derivatives are the main constituent of many interesting 3D metal–organic frameworks (MOFs), which show some excellent photophysical and materials properties. For more details see the Minireview by S. Konar et al. on page 5858 .